Bilirubin metabolism: delving into the cellular and molecular mechanisms to predict complications - Sadhana Kumbhar; Manish Musale; Anas Jamsa (SpringerOpen, 2024)
Abstract Bilirubin is a metabolic product of heme, and an increase in its level may be toxic to the body. It may be conjugated or unconjugated. Encephalopathy is caused by unconjugated bilirubin has the ability to pass through the blood-brain barrier, entering the central nervous system. Conjugated forms of bilirubin result in biliary obstruction and a change in urine colour due to a decrease in excretion. Excessive hemolysis can result from hereditary and autoimmune diseases, deficient RBC membranes, enzyme deficiency, and hemoglobin structural anomalies. In this review, we summarize all the possible mechanisms and complications regarding bilirubin. Cellular and molecular functions and mechanisms of bilirubin are explained, followed by several complications viz neurotoxicity, auditory dysfunction, and nephrotoxicity. The cause of bilirubin-induced neuronal cell damage is likely due to the elevated levels of unconjugated bilirubin in plasma, mitochondrial, and endoplasmic reticulum (ER) membranes. These disruptions in the membranes could lead to harmful effects such as neuronal excitotoxicity, energy failure in mitochondria, or an increased concentration of calcium within the cells. At the cellular level, bilirubin exerts its toxic effect by disturbing the normal functioning of neuronal cells. Bilirubin's presence can cause certain inflammatory responses, resulting in the activation of proinflammatory cytokines. Additionally, research has demonstrated that bilirubin can negatively affect auditory abilities. It disrupts the integrity of auditory pathways, resulting in auditory dysfunction and potentially causing long-term hearing impairments in infants affected by it. In conclusion, a comprehensive understanding of the complications associated with unconjugated bilirubin in neonates is essential for improving clinical management and outcomes. Understanding the cellular and molecular pathophysiology of high bilirubin may lead to a new therapeutic approach.